Between memory and childhood, absence is a legacy - Follador, Ana Carolina (Revista do Colóquio, 2024)
This visual essay presents an account of the work “the first time I believed you loved me was on a cloudy day that never arrived”, a series of three photographs and a prose printed on raw cotton fabric, made between 2022 and 2024. The works arise from reflective processes, as an artist, around maternal deprivation and parental emotional abandonment that I experienced in childhood and adolescence. It is a set of artistic works with themes sensitive to affective memory, as well as the development of a personal narrative that seeks to return maternal affection that was absent from me.